Examining the Gender Dynamics of Green Grabbing and Ejido Privatization in Zacatecas, Mexico - Vázquez-García, Verónica; Sosa-Capistrán, Dulce María (Frontiers in Sustainable Food Systems, 2021)
The ejido is the most important form of collectively owned property in Mexico; approximately half of the country’s territory belongs to ejidatarios of whom women make up roughly twenty percent. Recent legal reforms aimed at privatizing the ejido are forcing ejidatarios/as to sell or rent their lands to corporations seeking to invest in oil, mining and energy production. This paper examines the gender impacts of land privatization for renewable energy generation in two ejidos of Zacatecas, Mexico: El Orito and Benito Juárez. The first agreed to rent their lands to a private company while the other did not. This paper analyzes the impact of land rentals by gender, economic status and age. Results show that land rentals benefitted a handful of ejidatarios, while the people affected the most include male stone miners, ejidatarias who were excluded from decision-making, and women who obtain food and fuel from ejido common lands. Land rentals augmented previously existing disparities by concentrating payments in a few men and by limiting the access to common lands of poor men and women. The paper calls for a gender intersectional approach to continue examining the differentiated impacts of ejido privatization in Mexico.